The shaman's apprentice : a tale of the Amazon rain forest - Cherry, Lynne (Harcourt Brace & Co., 1998)
Kamanya believes in the shaman's wisdom about the healing properties of plants found in the Amazon rain forest and hopes one day to be a healer for his people.